1985
DOI: 10.1016/0304-3959(85)90057-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of arthritis and pain behaviour following chronic administration of amitriptyline or imipramine in rats with adjuvant-induced arthritis

Abstract: Tricyclic antidepressants (TCAs) are used extensively to treat chronic pain in man without an adequate explanation for their activity. The purpose of the present study was to investigate this problem by testing the effect of chronic TCAs in an animal pain model: the arthritic rat. Sprague-Dawley rats with adjuvant-induced arthritis were injected daily for 4 weeks with amitriptyline (10 mg/kg) or imipramine (10 mg/kg) or saline, beginning 21 days after the induction of arthritis. Baseline evaluations were made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(22 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…Thus, Neurotropin may alleviate hyperalgesia through the activation of descending pain inhibitory systems regardless of different pathogenesis of hyperalgesia. Amitriptyline and imipramine, monoamine re-uptake inhibitors, have also been shown to clearly reduce pain behavior in adjuvant-induced arthritic rats (37,38). These reports support that the activation of the descending pain inhibitory pathway is useful for relief of chronic pain.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, Neurotropin may alleviate hyperalgesia through the activation of descending pain inhibitory systems regardless of different pathogenesis of hyperalgesia. Amitriptyline and imipramine, monoamine re-uptake inhibitors, have also been shown to clearly reduce pain behavior in adjuvant-induced arthritic rats (37,38). These reports support that the activation of the descending pain inhibitory pathway is useful for relief of chronic pain.…”
Section: Discussionmentioning
confidence: 63%
“…There are few reports concerning the analgesic efficacy after single administration of antidepressants in the CFA-induced arthritic rats, although it has been reported that chronic (4 weeks) administration of amitriptyline or imipramine does not modify the mechanical threshold measured with the paw pressure test (Butler et al, 1985). When the survey is extended to other inflammatory pain models, it has been reported that intrathecal amitriptyline reverses thermal hyperalgesia measured with the plantar test in the carrageenan-induced inflamed rats (Eisenach and Gebhart, 1995).…”
mentioning
confidence: 99%
“…The method to determine the numerical arthritis scores was similar to those described previously (3,21). Peripheral joints were measured with a caliper and were assigned a score between 0 (no swelling) and 4 (Ͼ40 and Ͼ70% increase in diameter of the ankle and wrist joints, respectively).…”
Section: Methodsmentioning
confidence: 99%